ENVIRONMENTAL DEVELOPMENT IN UZBEKISTAN: MAIN PROBLEMS AND THEIR SOLUTIONS - Dildora Abdurakhmanovna Makhkamova (Western European Studies, 2024)
The article reflects on the environmental problems of Uzbekistan and ways to solve them. The role and importance of renewable energy sources as a solution to environmental problems are emphasized
Keywords: ecological economics; renewable energy sources; environment